Putting Practice into Theory: Ruth Sullivan’s Contribution to Legislative Scholarship, Practice, and Teaching - Keyes, John (Ottawa Law Review / Revue de droit d’Ottawa, 2024)
This article provides an account of Ruth Sullivan’s contribution to legislative scholarship and practice as a law professor and a legal practitioner, perhaps most notably as the author of five editions of the most widely cited text on legislative interpretation in Canada: The Construction of Statutes.Her writing on the methodology for drafting and interpreting legislation, and her teaching of these subjects has had an enormous impact and continues to be felt in the continuing citation of her work. Legislative methodology receives far too little scholarly attention in Canada despite the permeation of legislation in nearly every area of law. Ruth Sullivan’s work is a powerful reminder of its significance and the need to pay attention to its practice and evolution.